PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN DAMPAKNYA - Dewi, I Gusti Ayu Ratih Permata; Putri, Putu Yudha Asteria; Nugraha, Putu Gede Wahyu Satya (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2020)
This study uses a qualitative descriptive approach that aims to analyze CSR disclosures and their impact. The impact is seen from the financial and non-financial side. The financial side will be measured using profit margin, which is to compare the level of profit and sales. The non-financial side will be measured by seeing the reorder from customers and market expansion. Whereas the measurement of Corporate Social Responsibility (X) will be carried out using a checklist based on GRI G4 with economic categories, environmental categories, and social categories dimensions of labor practices and work comfort. CSR measurement is done by giving a value of 1 on the statement made by the owner or manager of MSME and giving a value of 0 on a statement that was not made by the owner or manager of MSME. After the checklist is carried out, the Corporate Social Responsibility Index (CSRi) will be calculated to determine the level of CSR implementation carried out. The research location was chosen in the Regency of Badung precisely at the UMKM artshop in the Nusa Dua area. The results of the study found that the level of implementation that has been carried out by the owner or manager of the artshop who became respondents in this study is included in the high category. CSR disclosure that has been carried out largely supports the financial side and non-financial side.